Estrutura populacional de florestas de Polylepis Ruiz & Pav. e o padrão de parasitismo por Tristerix chodatianus (Patschovsky) Kuijt ao longo de um gradiente altitudinal nos Andes Centrais do Peru - Almonacid, Marco Aurelio Arizapana (2018)
In the Andes, at high altitudes, the Polylepis spp. forests occur as one of the main ecosystems in the Andean region. In addition to their fragility to climate change, as montane forests, they are also threatened by other factors such as overexploitation, soil erosion, fire, and the advancement of agricultural frontiers. Even now there is a significant lack of data on these forests. Therefore, the spatial structure and anatomical attributes of two forests, the Polylepis incana Kunth forest and the Polylepis flavipila (Bitter) M. Kessler & Schmidt-Leb were evaluated. The population structure and parasitism pattern of Tristerix chodatianus in both forest populations was also investigated along the altitudinal gradient, in the Reserva Paisajistica Nor Yauyos Cocha, Laraos, Lima-Peru. Three transects with a width of 20 m were sampled for each species, from the beginning of the forest (the lowest part) to the tree line (the highest part). The samples comprised all individuals with a diameter at ground level superior or equal to 5 cm from which information about the spatial position, height, number of individuals, and basal area was obtained. As the altitude and slope increased, there was an increase in the basal area and diameter of P. flavipila individuals. The results indicate that the slope, altitude, presence of livestock and trails influence the occurrence and structure of Polylepis forests population. On the other hand, most of the response variables did not affect the anatomical attributes of the species evaluated, they showed marked differences in attributes only regarding altitude. From the same transects, samples of T. chodatianus individuals were used to study the population structure in order to evaluate and compare the population structure and pattern of parasitism along the environmental gradient. All trees (parasitized or not) with a diameter at ground level superior or equal to 5 cm were sampled from which was obtained spatial position, total height, diameter at ground level, number of twigs, and length of the longest twig. The total height differed between parasitized and non-parasitized individuals in both species, with parasitized trees presenting greater heights when compared to the non-parasitized ones. Both species showed an aggregated distribution pattern, probably related to the behavior of the disperser bird. Larger P. flavipila trees (in diameter and height) are more parasitized, while the higher presence of the parasite in P. incana is related to the increase in altitude. Our results contribute to the understanding on how T. chodatianus is distributed and how altitude influences its growth in mountainous environments.